Down Syndrome and Quality of Life: A Case Report - L. Schroeder, Hilary; Joanes, Marianinha; Small, Andre; Maramraj, Raghu (International Journal of Medical Students, 2015)
Background: Quality of life is considered a crucial component to the well-being of patients with Down syndrome. The strength of quality care through stable social and psychological interactions has built a framework for a positive well-being for patients with Down syndrome, improving their quality of life. Case: A 55-year-old African American female with a history of Down syndrome, congenital heart disease, and newly-diagnosed early onset Alzheimer’s disease presented with an arm contusion resulting from regular caretaking. The patient’s history was reviewed, and the complexity of her condition was discovered. While a subset of Down syndrome patients have cardiac complications and others have early-onset Alzheimer’s, our patient had both. We believe this complicated her condition. After the diagnosis of Alzheimer’s was made, the caregivers noticed a significant decline in her ability to communicate and continue day-to-day activities. Despite the decline in functions, a positive mood was apparent. Conclusion: Multiple medical interventions, along with strong family support, positively contributed to the patient’s quality of life. Therapies targeting cognition could result in the maintenance of quality of life and, ultimately, lower health care costs.